PENGGUNAAN METODE RESITASI DALAM MENINGKATKAN HASIL BELAJAR SISWA MADRASAH IBTIDAIYAH (MI) BINA INSANI KEC. GUNUNG LABUHAN KAB. WAY KANAN TAHUN 2019/2020 (STAI Al-Ma`arif Way Kanan Lampung, 2021)
ABSTRACT Based on the results of the researcher's pre-survey, in the results of the daily test results for the Islamic Education Subject for the 2019/2020 Academic Year, there were some students who had not yet completed it because the online learning process was not fully understood by students. Based on this, the formulation of the problem in this study is: